2013
DOI: 10.1001/jamaoto.2013.4911
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Venous Thromboembolism in Patients With Head and Neck Cancer After Surgery

Abstract: Hospitalized patients with head and neck cancer not routinely receiving anticoagulation therapy after surgery have an increased risk of VTE. Bleeding complications are elevated in patients receiving postoperative anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 38 publications
4
82
1
Order By: Relevance
“…The anticoagulant therapy poses the risk of hematoma‐induced airway obstruction and subsequent flap crisis. Although, another study reported a 3‐6‐fold increased risk of VTE in oncologic patients and further increased to 20‐fold if they were treated surgically . This indicates that surgical oncology inpatients are a high‐risk group for VTE development.…”
Section: Discussionmentioning
confidence: 99%
“…The anticoagulant therapy poses the risk of hematoma‐induced airway obstruction and subsequent flap crisis. Although, another study reported a 3‐6‐fold increased risk of VTE in oncologic patients and further increased to 20‐fold if they were treated surgically . This indicates that surgical oncology inpatients are a high‐risk group for VTE development.…”
Section: Discussionmentioning
confidence: 99%
“…Although retrospective studies have shown a low risk of VTE (<2.4%), in general otolaryngology patients a prospective study at our institution demonstrated a 13% overall incidence of VTE in head and neck cancer surgical patients . Furthermore, this study also demonstrated that patients receiving anticoagulation had a significantly higher rate of bleeding complications (30.1% vs. 5.6%) including hematomas compared to patients without anticoagulation therapy.…”
Section: Introductionmentioning
confidence: 49%
“…The reported incidence ranges between 0.035% and 2.4%, Clayburgh el al. found the risk of VTE can be as high as 8% for patient with cancer in the only available prospective observational cohort study that involved 100 patients undergoing head and neck surgeries …”
Section: Introductionmentioning
confidence: 99%